Dreams of Germany : musical imaginaries from the concert hall to the dance floor - Gregor, Neil, 1969-; Irvine, Thomas (Berghahn Books, 2019)
"For many centuries, Germany has enjoyed a reputation as the 'land of music'. But just how was this reputation established and transformed over time, and to what extent was it produced within or outside of Germany? Through case studies that range from Bruckner to the Beatles and from symphonies to dance-club music, this volume looks at how German musicians and their audiences responded to the most significant developments of the twentieth century, including mass media, technological advances, fascism, and war on an unprecedented scale"-- Provided by publisher.
Keywords: Music -- Social aspects -- Germany -- History -- 20th century.; Music -- Germany -- 20th century -- History and criticism.; National characteristics, German.; Music -- German influences.; Musique -- Aspect social -- Allemagne -- Histoire -- 20e siècle.; Allemands.; MUSIC -- Genres & Styles -- Classical.; MUSIC -- Reference.; MUSIC -- History & Criticism.; Music; Music -- German influences; Music -- Social aspects; National characteristics, German; Germany; 1900-1999; Criticism, interpretation, etc.; History